Effect of operator experience and cementation strategies on the bond strength between fiber post and root dentin - Bergoli, César Dalmolin; Costa Lima, Julia Magalhães [UNESP]; Bottino, Marco Antonio [UNESP]; de Melo, Renata Marques [UNESP]; Valandro, Luiz Felipe (Taylor & Francis, 2017)
This study evaluates the influence of operator experience on the bond strength between fiber posts and root dentin using different cementation strategies. One hundred and twenty bovine teeth were selected, cleaned, disinfected, and sectioned at 15 mm of root length (apical–coronal). The root canals were prepared up to 12 mm and the apical portions were embedded with acrylic resin in plastic matrices. Thereafter, the teeth were randomly distributed to six operators (three with experience and three without experience). The operators performed cementation using two different cementation strategies: conventional (three-step etch-and-rinse adhesive; Scotchbond Multi-Purpose and RelyX ARC) or simplified (one-step self-adhesive resin cement; RelyX U200). Following cementation, each specimen was sectioned to obtain three slices (2 mm). Slices were submitted to the push-out test and failure analysis. Mean bond strength of each group was evaluated by the Student’s t-test (α = 0.05). Statistical analysis did not show any influence of operator experience or cementation strategy on the bond strength values. The principal mode of failure was adhesive between the resin cement and root dentin. Authors conclude that operators with different clinical experience could achieve similar values of bond strength between fiber posts and root dentin, independent of the cementation strategy (conventional or simplified).
Keywords: Bond strength; fiber post; push-out test; resin cement; root dentin